Hepatitis B virus-infected HepG2hNTCP cells serve as a novel immunological tool to analyze the antiviral efficacy of CD8+ T cells in vitro - Hoh, Alexander; Urban, Stephan (Journal of virology, 2015)
CD8+ T cells are the main effector lymphocytes in the control of hepatitis B virus (HBV) infection. However, limitations of model systems, such as low infection rates, restrict mechanistic studies of HBV-specific CD8+ T cells. Here, we established a novel immunological cell culture model based on HBV-infected HepG2hNTCP cells that endogenously processed viral antigens and presented them to HBV-specific CD8+ T cells. This induced cytolytic and noncytolytic CD8+ T-cell effector functions and reduction of viral loads.